The Influence Of Product Quality And Fanatism On The Purchase Decision Of Mie Lemonilo X Nct Dream Products - Febriyanti, Deliana; Casilam, Casilam; Suparman, Yusuf (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
This study aims to analyze the effect of product quality and fanaticism on purchasing decisions for Lemonilo x NCT Dream noodles. The approach used is quantitative with independent variables of product quality and fanaticism, and dependent variables of purchasing decisions. Primary data were collected through questionnaires from 100 respondents who were Indonesian NCTzens, using the non-probability sampling method and calculated using the Slovin formula. Data analysis was carried out using SPSS 26. The results showed that product quality and fanaticism significantly influenced purchasing decisions both partially and simultaneously. The coefficient of determination (Adjusted R Square) of 59.5% indicates that purchasing decisions are influenced by product quality and fanaticism, while 40.5% is influenced by other factors not studied.